Determinants of dietary diversity and its relationship with the nutritional status of pregnant women. (2nd March 2021) - Saaka, Mahama; Mutaru, Sofo; Osman, Shaibu Mohammed
Abstract: There is little information regarding factors that determine dietary diversity among pregnant women in Ghana. The present study, therefore, sought to assess the independent predictors of dietary diversity and its relationship with nutritional status of pregnant women in the Northern Region of Ghana. The present study was an analytical cross-sectional survey involving 423 pregnant women in different stages of gestation. The 24-h dietary recall method was used to assess minimum dietary diversity for women (MDD-W), and nutritional status was assessed using mid-upper arm circumference (MUAC) measurements. Binary logistic regression was performed to assess the association between maternal dietary diversity and maternal thinness and a P value of <0⋅05 was considered statistically significant. Of the 423 women, 79⋅9 % (95 % CI 76⋅1, 83⋅7) met the MDD-W and the prevalence of undernutrition among the pregnant women was 26⋅0 %. The analysis showed that women of low household wealth index were 48 % less likely (AOR 0⋅52, CI 0⋅31, 0⋅88) of meeting the MDD-W, whereas women from households of poor food insecurity were 88 % less likely (AOR 0⋅12, CI 0⋅05, 0⋅27) of achieving the MDD-W. Women of low household size were three times more likely of meeting the MDD-W (AOR 3⋅07, CI 1⋅13, 8⋅39). MDD-W was not associated with maternal underweight during pregnancy. In conclusion, the results of the present study showed that food insecurity and not low MDD-W, associated with mothers' thinness (underweight) during pregnancy in peri-urban setting of Northern Ghana.